Political opportunity structures and the parliamentary entry of splinter, merger, and genuinely new parties. (August 2021) - Chiru, Mihail; Popescu, Marina; Székely, István Gergő
Drawing on an original sample of 351 elections held in new and consolidated democracies from 1960 to 2013, this article examines the likelihood that new parties gain parliamentary representation as a function of electoral system permissiveness and contextual factors that shape political entrepreneurs' perception of political opportunity. We distinguish between the success of genuinely new parties and that achieved by splinters or parties formed through mergers. We find that the district magnitude matters for the success of all three types of newcomers, while the electoral formula and proportionality matter only for the parliamentary entry of splinter parties. Another novel finding is that government instability facilitates the success of genuinely new and splinter parties. The analysis also shows that, irrespective of the type of transition, the more elections have taken place since then, the less likely it becomes that genuinely new parties and merger new parties enter parliament.